AlN/GaN MISHEMTs on Si with in-situ SiN as a gate dielectric for power amplifiers in mobile SoCs. (22nd December 2021) - Xie, Hanlin; Liu, Zhihong; Hu, Wenrui; Gao, Yu; Tan, Hui Teng; Lee, Kenneth E.; Guo, Yong-Xin; Zhang, Jincheng; Hao, Yue; Ng, Geok Ing
Abstract: AlN/GaN metal–insulator–semiconductor high electron mobility transistors (MISHEMTs) on silicon substrate using in situ SiN as gate dielectric were fabricated and their RF power performance at mobile system-on-chip (SoC) compatible voltages was measured. At a mobile SoC-compatible supply voltage of V d  = 3.5 V/5 V, the 90 nm gate-length AlN/GaN MISHEMTs showed a maximum power-added efficiency of 62%/58%, a maximum output power density ( P outmax ) of 0.44 W mm −1 /0.84 W mm −1 and a linear gain of 20 dB/19 dB at the frequency of 5 GHz. These results suggest that the in situ-SiN/AlN/GaN-on-Si MISHEMTs are promising for RF power amplifiers in 5G mobile SoC applications.